DPP-4 is expressed in human pancreatic beta cells and its direct inhibition improves beta cell function and survival in type 2 diabetes. (15th September 2018) - Bugliani, Marco; Syed, Farooq; Paula, Flavia M.M.; Omar, Bilal A.; Suleiman, Mara; Mossuto, Sandra; Grano, Francesca; Cardarelli, Francesco; Boggi, Ugo; Vistoli, Fabio; Filipponi, Franco; De Simone, Paolo; et al.
Abstract: It has been reported that the incretin system, including regulated GLP-1 secretion and locally expressed DPP-4, is present in pancreatic islets. In this study we comprehensively evaluated the expression and role of DPP-4 in islet alpha and beta cells from non-diabetic (ND) and type 2 diabetic (T2D) individuals, including the effects of its inhibition on beta cell function and survival. Isolated islets were prepared from 25 ND and 18 T2D organ donors; studies were also performed with the human insulin-producing EndoC-βH1 cells. Morphological (including confocal microscopy), ultrastructural (electron microscopy, EM), functional (glucose-stimulated insulin secretion), survival (EM and nuclear dyes) and molecular (RNAseq, qPCR and western blot) studies were performed under several different experimental conditions. DPP-4 co-localized with glucagon and was also expressed in human islet insulin-containing cells. Furthermore, DPP-4 was expressed in EndoC-βH1 cells. The proportions of DPP-4 positive alpha and beta cells and DPP-4 gene expression were significantly lower in T2D islets. A DPP-4 inhibitor protected ND human beta cells and EndoC-βH1 cells against cytokine-induced toxicity, which was at least in part independent from GLP1 and associated with reduced NFKB1 expression. Finally, DPP-4 inhibition augmented glucose-stimulated insulin secretion, reduced apoptosis and improved ultrastructure in T2D beta cells. These results demonstrate the presence of DPP-4 in human islet alpha and beta cells, with reduced expression in T2D islets, and show that DPP-4 inhibition has beneficial effects on human ND and T2D beta cells. This suggests that DPP-4, besides playing a role in incretin effects, directly affects beta cell function and survival. Highlights: An incretin system, including regulated GLP-1 secretion and locally expressed DPP-4, has been found in pancreatic islets. In the present study we have assessed the role of direct DPP-4 inhibition on beta cells from non-diabetic and type 2 diabetic individuals. We found that DPP-4 is expressed in human beta cells and its inhibition has several protective effects. This was due, at least in part, to reduced expression of NFKB and its target genes. Therefore, DPP-4, besides playing a role in incretin effects, can directly affect beta cell function and survival.